Oscola, a UK standard for legal citation - Meredith, S (Cambridge University Press, 2011)
OSCOLA, the Oxford Standard for the Citation Of Legal Authorities, was first devised in 2000. The fourth edition, published in November 2010, includes for the first time guidelines for citing Scottish, Irish and Welsh cases and legislation, historical legal sources and new media such as blogs. It also provides more extensive general advice about using quotations, managing and cross-referencing footnotes and organising bibliographies and tables of cases and legislation. OSCOLA can be used in conjunction with bibliographic software such as Endnote and is becoming the UK national standard for legal citation.